The physics of everyday phenomena : a conceptual introduction to physics - Griffith, W. Thomas; Brosing, Juliet Wain , 1953- (McGraw-Hill, 2012)
Introduces students to the basic concepts of physics using examples of common occurrences in everyday life. This book draws the reader into a dialogue about the ideas of physics. It is suitable for those who are interested in exploring the nature of physics and explanations of everyday physical phenomena